Research in the Process of Education of Medical Students Shaping Their Abilities - Abdullayeva Sanobar Berdiyevna; Makhmudmurodova Marjona Akramovna; Ravshanova Parviza Olmasovna (Genius Journals, 2023)
Studies of medicine is the basis and research in the field achievements wide to the population displayed medical help quality in raising solution doer role he plays In general when medicine field students by research to do abilities development process research programs study programs within combine or sure activities encouragement or sure defined to the plan looking course during distributed materials through done increase can Har how another competent persons like , medicine of students too qualification determination for research abilities evaluation for criterion to be a must Summary by doing to say maybe medicine to students bachelor during scientific research skills development for enough in quantity study possibilities to be given need
Keywords: Assessment; ability; curriculum; medical students